The maximisation utilisation of space through application of narrow aisle system in Sime Swede Distribution Services Sdn. Bhd. / Tengku Intan Alirah Tengku Mohamad Ali - Tengku Mohamad Ali, Tengku Intan Alirah (1994)
Sime Swede Distribution Services Sdn. Bhd. commenced operation in June 1992. It provide modern and sophisticated public warehousing and distribution services. This company is tipped to make a significant impact on the warehousing and distribution industry in Malaysia.